PENGGUNAAN E-WALLET OVO PERSPEKTIF ULAMA SYAFI'IYAH - Khadijatul Musanna; Riadhus Sholihin; Maula Sari (Asy-Syari'ah, 2022)
This study analyzes the status of the legal status that applies to payments through OVO based on the perspective of Ulama Syafi'yah. The research method used is descriptive qualitative, based on normative juridical regarding the laws applicable to OVO, analyzed conceptually using the opinions of Syafi'iyah Scholars. The results show that the payment system of the OVO application tends to use wadi'ah contracts, this can be seen from the elements, namely, contracts, objectives and objects of contracts that are clear and certain. Additionally, the object of the contract in the use of the OVO application has a feature in the form of a stored balance, so that at any time it can be taken back by the account owner without the need for permission from OVO as the application provider, this further strengthens the perception that OVO is oriented in the wadi'ah contract.